Long-Term Effects of Biochar Application With Reduced Chemical Fertilizer on Paddy Soil Properties and japonica Rice Production System - Gu, Wenqi; Wang, Yuning; Feng, Zhibo; Wu, Di; Zhang, Honggui; Yuan, Hechong; Sun, Yuanyuan; Xiu, Liqun; Chen, Wenfu; Zhang, Weiming (Frontiers in Environmental Science, 2022)
To clarify the effects of co-application of rice-straw biochar and different chemical fertilizer doses on a paddy soil properties and japonica rice production in Northeast China, a located-field experiment was adopted for 5 years. The treatments included fertilization (F, no biochar, control), and rice-straw biochar (7.5 t·ha-1) combined with different chemical fertilizer doses (100%, 80% and 60% that of F), set as CF, CF1 and CF2, respectively. The results showed that the co-application of biochar and chemical fertilizer after 5 years reduced soil bulk density, increased soil total and capillary porosity, changed the soil solid-liquid-gas ratio (increased the liquid and air ratios and decreased the solid ratio), and increased soil macroaggregates (>0.25 mm) and aggregate stability, which enhanced soil physical properties. Furthermore, the co-application improved soil pH and soil enzyme activity (urease, sucrase and catalase) and had a significant effect on promoting SOM. The soil total N, P and K of CF and CF1, were 23.48%, 47.28%, 26.59% and 9.47%, 43.98%, 27.87% higher than those of the control, respectively. The soil available nutrients (N, P, K) increased in the co-application treatment, shown as the nitrogen was promoted higher in the early growth of rice, while the phosphorus and potassium exhibited greater higher in the late growth. With the soil amendment, the co-application increased the rice plant height and dry matter accumulation, and the CF and CF1 increased yield by 5.78% and 2.41%, respectively, by increasing the rice effective panicles, grains per panicle and seed setting rate. Co-application of biochar and chemical fertilizer could significantly amend soil properties and reduce chemical fertilizer use to ensure rice grain output, which has important significance for enhancing sustainable soil and crop productivity.